Transmission pathway of Enterobacteriaceae from reared fish and surrounding environment to water body in Batang Ai reservoir, Sarawak, Borneo - Lihan, Samuel; Furzanne, S.V; Toh, S.C.; Nurul Asyiqin, J. (Rynnye Lyan Resources, 2022)
This study was aimed to determine the genetic distribution and characteristics of the bacterial family in the Batang Ai reservoir and their possible sources of transmission into the lake water. Surface water samples were collected from twenty-seven sampling points scattered around the Batang Ai reservoir and four fish samples were obtained from an aquaculture farm located within the water reservoir. The samples were plated on Violet Red Bile Agar (VRBA) plates for the isolation of Enterobacteriaceae. A total of 141 bacterial colonies were isolated from the culture plates and subjected to (GTG)5 PCR analysis to determine the genetic similarities among the isolates. A dendrogram was plotted based on the (GTG)5 PCR patterns and the representative isolates were selected for identity confirmation using 16S rRNA sequencing. Based on the sequencing, five genera of Enterobacteriaceae were identified as Enterobacter, Escherichia, Shigella, Klebsiella and Pseudocitrobacter, consisting of 12 identified species, namely Enterobacter hormaechei, E. hormaechei subsp. xiangfangensis, E. cloacae, E. cloacae subsp. dissolvens, E. kobei, E. tabaci, Shigella boydii, S. flexneri, Pseudocitrobacter faecalis, Escherichia fergusonii, E. coli and Klebsiella pneumoniae. A total of 14 antibiotics from seven anti-microbial classes including penicillins, cephems, monobactams, aminoglycosides, tetracyclines, quinolones and fluoroquinolones, and phenicols were tested against the isolates. A total of seven species within the isolates were found to have multiple antibiotic resistance (MAR) index below 0.2, suggesting those isolates were derived from low risk of antibiotics contamination sources. With the exception of ampicillin and tetracycline, all antibiotics have 25% or less bacterial species displaying resistance. Most (70%) of the bacterial species showed resistance toward ampicillin. The fish isolates demonstrated multiple antibiotic resistance indexes ranging from 0.214 to 0.5. The presence of multiple antibiotic-resistant bacteria in the water reservoir may pose the risk of antibiotic-resistant bacterial infections through water-related activities and consumption of fish harbouring antimicrobial resistance bacterial species. It was proven that Enterobacteriaceae were transmitted from the activities and surrounding environments to the water reservoir, thus it is proposed that a guideline for activities to be carried out in the water reservoir is created and imposed.